PERSEPSI ANAK PETANI TERHADAP PEKERJAAN DI SEKTOR USAHA TANI PADI DI DESA TELANG JAYA KECAMATAN MUARA TELANG KABUPATEN BANYUASIN - Yuliani, Ega; Adriani, Dessy; Bidarti, Agustina (Agros Journal of Agriculture Science, 2024)
Perception of rice farmers' children in continuing their family's rice farming business is very influential in all forms of sustainability of existing rice farming businesses. Rice farming activities will run smoothly if young farmers are willing to actively participate in making their contribution to rice farming activities in Telang Jaya Village.The purpose of the research are to: 1) Analyze the characteristics of rice farmer’s children those who are still continuing school and those who are not continuing their education anymore, 2) Analyze the perceptions of rice farmer’s children those who are still continuing school and those who are not continuing their education anymore in continuing rice farming, and 3) Analyze what factors influence perceptions of rice farmer’s children in continuing rice farming. Sampling method that used in this research was stratified random sampling method, where there are two layers of farmer’s children, the first layer is farmer’s children who are in junior high school and senior high school who are still in scholl, and the second layer is farmer’s children who should be in junior high school and senior high school but are not continuing their education anymore. The result of this research 1) Characteristics of rice farmer’s children who are still continuing school, the most dominant age criteria is 13-15 years (52.50%), for education the number is the same between junior high scholl and senior high school, namely the same 20 of rice farmer’s children, the average length of participation in family farming is 6-8 years (72.50%), and the gender of of rice farmer’s children is dominated by 24 women (60.00%), and Characteristics of rice farmer’s children who are not continuing their education anymore, the most dominant age criteria is 16-18 years (80.00%), for education the most dominant is senior high school as many as 16 people (80.00%), the average length of participation in family farming is 6-8 years (75.00%), and the gender of rice farmer’s children is dominated by 12 men (60.00%), 2) The interest of rice farmer’s children who are still continuing school is in the criteria of less interest, and the interest of rice farmer’s children who are not continuing their education anymore is at Interest criteria, 3) Factors that influence the interest of rice farmer’s children in continuing rice farming, at logit 1 (less interested) which have a significant influence are education and socialization from the family. Meanwhile, in logit 2 (Interested), the significant influence is socialization from the family.Key-words: interest, perception, sustainability of rice farming business INTISARIPersepsi anak petani padi dalam melanjutkan usahatani padi milik keluarga sangat berpengaruh dalam segala bentuk keberlanjutkan usahatani padi  yang ada. Kegiatan usahatani padi akan bejalan dengan lancar jika petani muda mau ikut serta berpartisipasi aktif dalam memberikan kontribusi mereka untuk kegiatan usahatani padi di Desa Telang Jaya Kecamatan Muara Telang, Kabupaten Banyuasin. Tujuan dari penelitian ini adalah untuk: 1) Menganalisis karakteristik anak petani padi yang masih melanjutkan sekolah dan yang tidak melanjutkan sekolah lagi, 2) Menganalisis persepsi anak petani padi yang masih melanjutkan sekolah dan yang tidak melanjutkan sekolah lagi dalam melanjutkan usahatani padi,  dan 3) Menganalisis faktor apa yang memengaruhi persepsi anak petani padi dalam melanjutkan usahatani padi. Metode penarikan contoh yang digunakan adalah metode sampel acak berlapis, di sini terdapat  dua lapisan anak petani, lapisan pertama adalah anak petani yang duduk di bangku SMP-SMA yang masih sekolah dan lapisan kedua adalah anak petani yang seharusnya duduk di bangku SMP-SMA namun tidak melanjutkan sekolahnya lagi. Hasil penelitian menunjukkan bahwa: 1) Karakteristik anak petani padi yang masih melanjutkan sekolah pada kriteria umur yang paling dominan adalah 13-15 tahun (52,50%), untuk pendidikan memiliki jumlah yang sama antara SD dan SMP, yaitu sama-sama 20 anak petani padi,  lama keikutsertaan dalam usahatani keluarga rata-rata adalah 6-8 tahun (72,50%), dan jenis kelamin anak petani padi didominasi oleh perempuan sebanyak 24 orang (60,00%), sedangkan karakteristik anak petani padi  yang tidak melanjutkan sekolah lagi pada kriteria umur yang paling dominan adalah 16-18 tahun (80,00%), untuk pendidikan yang paling dominan adalah SMA sebanyak 16 orang (80,00%),  lama keikutsertaan dalam usahatani keluarga rata-rata adalah 6-8 tahun (75,00%), dan jenis kelamin anak petani padi didominasi oleh laki-laki sebanyak 12 orang (60,00%), 2) Minat anak petani yang masih melanjutkan sekolah dalam melanjutkan usahatani padi berada pada kriteria kurang berminat, dan minat anak petani yang tidak melanjutkan sekolah lagi dalam melanjutkan usahatani padi berada pada kriteria berminat, 3) Faktor yang memengaruhi minat anak petani dalam melanjutkan usahatani padi, pada logit 1 (kurang berminat) yang berpengaruh signifikan adalah pendidikan dan sosialisasi dari keluarga. Pada logit 2 (berminat) yang berpengaruh signifikan adalah sosialisasi dari keluarga. Kata kunci: keberlanjutan usahatani padi, minat, persepsi